2019
DOI: 10.1002/mnfr.201900343
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Eicosapentaenoic Acid Feeding Decreases Placental Lipid Deposition and Improves the Homeostasis of Oxidative Stress Through a Sirtuin‐1 (SIRT1) Independent Manner

Abstract: Scope: Maternal obesity has been associated with increased placental lipotoxicity and impaired mitochondrial function. Sirtuin-1 (SIRT1) is an important regulator of both lipid metabolism and mitochondrial biogenesis. The present study aims to determine whether supplementation of the maternal diet with eicosapentaenoic acid (EPA) can decrease placental lipid deposition and improve antioxidant ability, in a SIRT1-dependent manner. Methods and results: Pregnant SIRT1 +/− mice (mated with male SIRT1 +/− ) are fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The mechanism of action included the upregulation of the c‐kit protein and the phosphorylation of the ERK1/2, Akt, and endothelial nitric oxide synthase signaling molecules (Chiu et al., 2014 ). Studies on rodents also found that the consumption of n ‐3 PUFAs induced the formation of new blood vessels in the mice ischemia–reperfusion model and subsequent placental development (Chiu et al., 2014 , Peng et al., 2019 ). Consistent with these studies, we found that a low dose of C20:5 significantly promoted tube formation in PIEC in vitro, which suggested that n ‐3 PUFAs might be effective fatty acid that could relieve placental lipotoxicity and promote angiogenesis in the placenta of sows.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mechanism of action included the upregulation of the c‐kit protein and the phosphorylation of the ERK1/2, Akt, and endothelial nitric oxide synthase signaling molecules (Chiu et al., 2014 ). Studies on rodents also found that the consumption of n ‐3 PUFAs induced the formation of new blood vessels in the mice ischemia–reperfusion model and subsequent placental development (Chiu et al., 2014 , Peng et al., 2019 ). Consistent with these studies, we found that a low dose of C20:5 significantly promoted tube formation in PIEC in vitro, which suggested that n ‐3 PUFAs might be effective fatty acid that could relieve placental lipotoxicity and promote angiogenesis in the placenta of sows.…”
Section: Discussionmentioning
confidence: 97%
“…The placenta is a highly vascularized tissue that provides all the nutrients necessary for fetal growth (Meher et al., 2015 , Saben et al., 2014 ). During pregnancy, placental angiogenesis is critical to enable the effective exchange of nutrients and waste between mother and fetus (Peng et al., 2019 , Peng et al., 2019 ). Similar to other tissues, placental angiogenesis could be divided into the following steps: endothelial cell proliferation and migration, tube formation, and vessel elongation and maturation (Chen et al., 2017 , Kaufmann et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…It deacetylates FoxO1, promoting autophagy, and also deacetylates ATG proteins. SIRT1 is cardioprotective, but chronic elevated levels can be detrimental, leading to oxidative stress, apoptosis, and cardiomyopathy [148][149][150][151][152] . Proper regulation of SIRT1 is necessary for maintaining cardiac function [150,153,154] .…”
Section: Main Intracellular Mechanisms Underlying Autophagymentioning
confidence: 99%
“…SIRT1 is cardioprotective, but chronic elevated levels can be detrimental, leading to oxidative stress, apoptosis, and cardiomyopathy [148][149][150][151][152] . Proper regulation of SIRT1 is necessary for maintaining cardiac function [150,153,154] . The Sirtuin family is also essential for the regulation of the mitochondrial unfolded protein response (mtUPR), one of the first stressprotective responses started by mitochondrial dysfunction [155] , which clears or repairs misfolded proteins in order to mitigate the damage [156][157][158] .…”
Section: Main Intracellular Mechanisms Underlying Autophagymentioning
confidence: 99%
“…LA attenuates acroleininduced oxidative stress [16]. EPA can decrease ROS to attenuate oxidative stress [17][18][19]. In addition, DHA protects photoreceptors from oxidative stress [20].…”
Section: Introductionmentioning
confidence: 99%